[OP.3A.07] CHANGES IN HUMAN RENAL CORTICAL AND MEDULLARY PERFUSION AND BLOOD OXYGENATION (BOLD) LEVELS DURING SYMPATHETIC ACTIVATION, MEASURED WITH CONTRAST-FREE, MR-BASED METHODS. (September 2017) - Andersen, U.; Haddock, B.; Larsson, H.B.
Abstract : Objective: Renal medullary flow abnormalities have been implicated in the pathogenesis of primary and secondary hypertension. Renal sympathetic nerve activity is involved in the regulation of medullary perfusion, and ablation of efferent sympathetic nerve activity by renal denervation drastically lowers the blood pressure in some hypertension patients. Using MRI, we have measured changes in renal flow, medullary and cortical perfusion and oxygenation in healthy humans during activation of the sympathetic nerve system with hand grip exercise. Figure. No caption available. Design and method: 10 healthy subjects had identical examinations on two occasions in a 3Tesla MR-scanner. On each occasion subjects performed 5 minutes hand-grip tests in the scanner to obtain continuous measurements of BOLD, perfusion and interleaved measurements of T2 * and renal artery flow. Flow measurements were obtained from phase-encoding imaging, perfusion using arterial spin labeling (ASL) and both BOLD and T2 * using gradient echo images. Results: Hand-grip induced a decrease of flow in the renal artery by 17.4+/−7%, and in the renal medulla an increase of oxygenation (T2 * ) by 22+/− 9% despite a drop in perfusion −12 +/−5% (p < 0.05). In the renal cortex we noted nonsignificant decreases of perfusion and oxygenation (T2 * ) of −2.5+/−2.5% and −1.4+/−4%, respectively. A significant relation (R2 = 0.58, p < 0.01) was noted between the resting systolic blood pressure and the decrease of flow in the renal artery during hand-grip. Conclusions: Radiation- and contrastfree MR measurements of renal artery flow, BOLD and perfusion in renal cortex and medulla, acquired for the first time in humans during hand grip testing, were consistent with a sympathetically mediated decrease in renal artery flow and cortical flow and oxygenation. In the medulla, perfusion decreased and oxygenation increased, interpreted as being due to a reduction of distal sodium delivery and hence the reabsorptive workload. A correlation between resting blood pressure and renal artery flow response to hand grip exercise could indicate an increased sensitivity of renal flow response to sympathetic activaton in subjects with high blood pressure. These techniques may be useful to asses patients having primary hypertension and renal artery stenosis.